MODELS OF CANING IN ACEH AND MALAYSIA: A COMPARISON - Hamdani Hamdani; Muhammad Nasir; Muhammad Helmi Md Said; Laila M. Rasyid; Putri Ismalinda (Fakultas Hukum, Universitas Diponegoro, 2023)
One of the punishments imposed on the offender in Aceh is caning based on Qanun Jinayah. This study compares the implementation of caning in Aceh and Malaysia. This study uses qualitative research methods with normative and empirical juridical approaches by applying prescriptive-analytic methods. The implementation of caning punishment in Aceh is the responsibility of prosecutor's office, the executor of wilayatul hisbah. The execution in an open place witnessed by the public according to the purpose of punishment and provides deterrence effect for the community and the convict. Based on regulation, implementation of caning punishment may not be accessible to children, but this cannot be fully implemented due to different district/city government policies. Caning in Malaysia is carried out in prison and witnessed by a few Muslims to achieve the purpose of punishment. In accordance with the conditions of local wisdom in Aceh and Malaysia. The Aceh government needs to provide a deterrent effect on convicts, caning is carried out at the convict's domicile and in accordance with applicable laws and committed to supporting Islamic law, including budget contributions.